SHORT NOTICES - Brooke, George J. (Journal of Semitic studies, 2003)
The Romanian Version of the Testament of Abraham: Text, Translation, and Cultural Context (Society of Biblical Literature Early Judaism and Its Literature 19) Nicolae Roddy , Society of Biblical Literature, Atlanta 2001. Pp. x + 140. Price: $39.95 hardback. ISBN: 0-58983-012-1.